The Impact of the Existence of Universitas Islam Negeri Raden Intan Lampung on the Economy of the Surrounding Community According to Maqasid al-Shari'ah Perspective - Hanif, Hanif; Susanto, Is; Mukri, Moh. (Universitas Islam Negeri Raden Intan Lampung, 2023)
The infrastructure development planned by the government is not only for infrastructure development for the needs of society in general, but in the education sector the government is also making changes and developments. The aim of it is to develop higher education so the implementation of education is carried out dynamically and conducively that education can carry out its function as a means of improving the welfare of society and developing the country's economy which later became the background of this conducted research. This study is field research with a qualitative approach. There were 60 respondents as data sources, data collection tools used observation and interviews, while data analysis used a qualitative approach and conclusions were drawn using a deductive thinking framework. Research findings show that the existence of UIN Raden Intan Lampung is not only an education center, but also a driving force for the local economy and an agent of positive change in improving the economy of the surrounding community. The existence of UIN Raden Intan Lampung can be interpreted as an instrument that can support the achievement of maqasid al-syari'ah goals for the good and welfare of humanity.